2018
DOI: 10.1111/jan.13847
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of nurses’ career choices: The importance of career expectations on employment in care of older people

Abstract: The likelihood of moving into care of older people increases with time in nursing careers and relates to nurses' career expectations such as achieving a leadership position and working part-time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
2
11
0
3
Order By: Relevance
“…This result seems logical as by choosing to work in the mental health field, students opt for a nursing field where they think they will feel comfortable providing their care and establishing a nurse–patient relationship. Therefore, they are more available to interact with people with mental illness [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result seems logical as by choosing to work in the mental health field, students opt for a nursing field where they think they will feel comfortable providing their care and establishing a nurse–patient relationship. Therefore, they are more available to interact with people with mental illness [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The StudData set offers suitable data for our purpose, but the insights need further validation to become conclusive evidence. Although we suggest carefulness, the items have been used in previous studies that have examined the motivation (Aamodt & Jensen, 2002; Nesje, 2014) and career expectations in nursing students (Abrahamsen, 2019; Abrahamsen & Drange, 2014). As the StudData survey has contributed to numerous publications, 3 they were considered suitable for the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…in previous studies that have examined the motivation (Aamodt & Jensen, 2002;Nesje, 2014) and career expectations in nursing students (Abrahamsen, 2019;Abrahamsen & Drange, 2014) The present study's cross-sectional design was well suited to analyse a great deal of data on the topic. This type of design often provides data on complex relationships, and there may be unknown factors that affect the variables (Polit & Beck, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…Our findings demonstrated that factors often associated with extrinsic need satisfaction (e.g., the need for security and predictability), such as familial obligations (e.g., children under the age of 18) and permanent positions, are the only factors differentiating nurses in the community health service from nurses in the specialist health service. It is conceivable that the difference between the groups related to the children factor may be because the nurses who work in the specialist health service experience an imbalance between having children and their work (Yamaguchi, Inoue, Harada, & Oike, 2016), which in turn motivates the nurses to search for jobs where they experience an opportunity to balance their work and family life (Abrahamsen, 2019; Gautun, Øien, & Bratt, 2016; Yamaguchi et al., 2016). Since nurses highly value a permanent position and holding a temporary position may experience insecurity related to the job situation (Andresen et al., 2017), it is conceivable that nurses searching to balance their work and family life choose to work in the community health service due to the sectors significantly higher proportion of nurses in permanent positions.…”
Section: Discussionmentioning
confidence: 99%